2015
DOI: 10.1007/s00540-015-2108-7
|View full text |Cite
|
Sign up to set email alerts
|

Challenge to pediatric anatomical variation : Can we draw the ideal line on the pediatric I-gel?

Abstract: Results suggested that it is possible to draw an ideal line on the I-gel with sizes 1.5 and 2 only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The results revealed that I-gel insertion length was related to patient height for paediatric sizes 1.5 and 2.0, but not for size 2.5. Considering our own results, which demonstrated the superiority of the ProSeal LMA over the I-gel in infants, we believe that it is necessary for further studies to investigate the use of the I-gel in infants under the same method used by Abukawa et al ( 1 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The results revealed that I-gel insertion length was related to patient height for paediatric sizes 1.5 and 2.0, but not for size 2.5. Considering our own results, which demonstrated the superiority of the ProSeal LMA over the I-gel in infants, we believe that it is necessary for further studies to investigate the use of the I-gel in infants under the same method used by Abukawa et al ( 1 ).…”
Section: Discussionmentioning
confidence: 89%
“…As the oropharyngeal-laryngeal arch is variable in children, it is recommended that the paediatric I-gel be inserted until resistance is felt. Abukawa et al ( 1 ) investigated the relationship between the insertion length of I-gel sizes 1.5, 2 and 2.5, along with the patients’ heights and weights. The size 1 I-gel was not assessed in the study, as the patient cohort did not require that size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation